Current Research of Graphene-Based Nanocomposites and Their Application for Supercapacitors - Santosh K. Tiwari; Anukul K. Thakur; Amrita De Adhikari; Yanqiu Zhu; Nannan Wang (Nanomaterials, 2020)
This review acmes the latest developments of composites of metal oxides/sulfide comprising of graphene and its analogues as electrode materials in the construction of the next generation of supercapacitors (SCs). SCs have become an indispensable device of energy-storage modes. A prompt increase in the number of scientific accomplishments in this field, including publications, patents, and device fabrication, has evidenced the immense attention they have attracted from scientific communities. These efforts have resulted in rapid advancements in the field of SCs, focusing on the development of electrode materials with features of high performance, economic viability, and robustness. It has been demonstrated that carbon-based electrode materials mixed with metal oxides and sulfoxides can perform extremely well in terms of energy density, durability, and exceptional cyclic stability. Herein, the state-of-the-art technologies relevant to the fabrication, characterization, and property assessment of graphene-based SCs are discussed in detail, especially for the composite forms when mixing with metal sulfide, metal oxides, metal foams, and nanohybrids. Effective synthetic methodologies for the nanocomposite fabrications via intercalation, coating, wrapping, and covalent interactions will be reviewed. We will first introduce some fundamental aspects of SCs, and briefly highlight the impact of graphene-based nanostructures on the basic principle of SCs, and then the recent progress in graphene-based electrodes, electrolytes, and all-solid-state SCs will be covered. The important surface properties of the metal oxides/sulfides electrode materials (nickel oxide, nickel sulfide, molybdenum oxide, ruthenium oxides, stannous oxide, nickel-cobalt sulfide manganese oxides, multiferroic materials like BaMnF, core-shell materials, etc.) will be described in each section as per requirement. Finally, we will show that composites of graphene-based electrodes are promising for the construction of the next generation of high performance, robust SCs that hold the prospects for practical applications.